La lógica del don en el horizonte de la sociedad civil - Galindo García, Ángel (Veritas, 2013)
In this article I discuss the encyclical Caritas in veritate, Benedict XVI having as key to reading the market, the state and civil society, which form a union in which the osmotic person, free and responsible, can be expressed in terms of development. The market goes through the contract, the State by just laws and civil society for the gift and gratuity. In this context, civil society is essential to not close man between the market and the state.